2014
DOI: 10.3892/mmr.2014.2558
|View full text |Cite
|
Sign up to set email alerts
|

miR-193b directly targets STMN1 and uPA genes and suppresses tumor growth and metastasis in pancreatic cancer

Abstract: Pancreatic cancer has the poorest prognosis among all cancer types, due to its late diagnosis and the lack of effective therapies. Therefore, identification of novel gene targets, which are differentially expressed in pancreatic cancer and functionally involved in the malignant phenotype, is critical to achieve early diagnosis and develop effective therapeutic strategies. microRNAs (miRNAs) are small non-coding RNAs, which negatively regulate the expression of their targets. Due to their various targets, miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…2). All four of these miRNAs have been reported as dysregulated in other cancer types, including colorectal cancer and pancreatic cancer [19][20][21][22]. In particular, the validity of miR-193b-3p as a prognostic marker in OPSCC was previously reported and incorporated in our previous model for outcome prediction [8].…”
Section: Validation Of An Existing Mirna Prognostic Signaturementioning
confidence: 88%
“…2). All four of these miRNAs have been reported as dysregulated in other cancer types, including colorectal cancer and pancreatic cancer [19][20][21][22]. In particular, the validity of miR-193b-3p as a prognostic marker in OPSCC was previously reported and incorporated in our previous model for outcome prediction [8].…”
Section: Validation Of An Existing Mirna Prognostic Signaturementioning
confidence: 88%
“…MiR-193b is also highly expressed in head and neck squamous cell carcinoma and it was associated to a low disease-free survival in this pathology [33]. Conversely, miR-193b seems to be downregulated in NSCLC, in pancreatic cancer and in breast cancer, suggesting a possible role of this miRNA in the development of these tumors [34][35][36].…”
Section: Discussionmentioning
confidence: 98%
“…STMN1 is a 17-kDa cytoplasmic protein, which is also named as oncoprotein 18 (OP18) [41][42][43]. Previous research showed that STMN1 acted as an important regulator in cell cycle, proliferation, invasion and survival through regulating microtubule dynamics [44][45][46]. STMN1 was upregulated in several human tumors such as lung cancer, gastric cancer, oral squamous-cell carcinoma, colorectal tumor, gallbladder cancer and breast cancer [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%